Physico-Chemical Characteristics and Sensory Quality of Dry Fermented Sausages with Flaxseed Oil Preparations - Stajić Slaviša; Stanišić Nikola; Lević Steva; Tomović Vladimir; Lilić Slobodan; Vranić Danijela; Jokanović Marija; Živković Dušan (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to determine the extent of changes in physico-chemical and sensory properties of dry fermented sausages where pork backfat was partly replaced by flaxseed oil used as liquid (FXL), after encapsulation (FXE), and pre-emulsified with alginate (FXA) and soy protein isolate (FXI). During production and storage, similar pH values of all products were observed. FXL sausages had significantly lower (p<0.05) weight loss which led to significantly higher moisture content, significantly lower fat content, hardness and chewiness. Also, FXL sausages had the lowest grades in terms of sensory attributes, such as colour, odour, taste, texture and overall acceptability. Flaxseed oil preparations affected the parameters of instrumental colour analysis of sausages. All modified products had significantly higher yellowness (relative to control) and FXI sausages relative to other modified products. Regarding consumer sensory evaluation, FXA sausages stood out among modified products because all other modified products had significantly lower grades relative to control. The thirty-day storage period did not lead to significant changes (p>0.05) in any of the observed sensory characteristics.